Exposure of sexually explicit materials: the application of the existing laws in curbing the problem / Dhaniah Ahmad, Norasidi Nadziruddin and Ummal Remiza Khaja Mohideen. - Ahmad, Dhaniah; Nadziruddin, Norasidi; Mohideen, Ummal Remiza Khaja (Faculty of Law, 2006)
The growth and development of technology is flourishing and seems to be impressive from time to time with the new inventions derive from creative mind of the mankind, apparently. However, despite of the contributions from countries throughout the entire world are seen to be inevitable and encouraging benefiting the people in various ways, there are also defects apart of its contribution which may results in a negative manner and also cause disaster to the society as a whole, technically or morally. Specifically, the context or issue which we are focusing in this study is primarily about the borderless world which is known as the 'borderless world'. It has becomes an easy access territory, where there is almost no restriction at all. In other words, anyone may enter into the cyberspace or the Internet just through a click on the computer. The problem arising from the cyberspace nowadays is regarding the wide usage of unwanted website to acquire sexual or adult materials. As far as the study is concerned, the law pertaining it and its enforcement are being so weak and vulnerable, which has caused loopholes in the rules and regulations itself. In this legal research, we will analyze, discuss and look into the existing laws which are in practice in Malaysia with few comparisons with other countries like the United Kingdom and the United States. It is essential as it assists us to measure its effectiveness in order to be applied and adopted strictly. Besides that, stringent and prompt action by the government, non-governmental bodies, parents and the society need to strive hand in hand to combat and prevent before the exposure get more serious and worse.